2017
DOI: 10.1111/1365-2656.12608
|View full text |Cite
|
Sign up to set email alerts
|

Climatic conditions cause spatially dynamic polygyny thresholds in a large mammal

Abstract: The polygyny threshold (PT) is a critical transition point in the sexual selection process for many organisms in natural populations, characterizing when females choose to mate with an already mated male over an unmated one to improve fitness. Understanding its causes and consequences is therefore of high interest. While both theoretical and empirical work suggest that the degree of polygyny within a species is plastic and a function of male inequality, the functional relationship between underlying availabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 47 publications
3
23
0
Order By: Relevance
“…As demonstrated with our other work in this system (see Manning et al, ; Manning & McLoughlin, ), some horses were observed repeatedly over the study while others were observed only once in a season, leading to samples that were unequally distributed among the dominant males. Repeated counts of individuals within each year (xfalse¯=2.84,SD=1.43) were accounted for by first using the sum number of unique overlapping individuals in a given year to calculate annual measures of each selection metric associated with a dominant male, and also including individual male identity as the random effect intercept term in each model (Laird & Ware, ).…”
Section: Methodssupporting
confidence: 79%
See 4 more Smart Citations
“…As demonstrated with our other work in this system (see Manning et al, ; Manning & McLoughlin, ), some horses were observed repeatedly over the study while others were observed only once in a season, leading to samples that were unequally distributed among the dominant males. Repeated counts of individuals within each year (xfalse¯=2.84,SD=1.43) were accounted for by first using the sum number of unique overlapping individuals in a given year to calculate annual measures of each selection metric associated with a dominant male, and also including individual male identity as the random effect intercept term in each model (Laird & Ware, ).…”
Section: Methodssupporting
confidence: 79%
“…We predicted that limited freshwater availability would increase male mating inequality in the second episode because increased water requirements during reproduction, pregnancy, and lactation would heighten female mate choice under these conditions (Contasti, Tissier, Johnstone, & McLoughlin, ; Richard, Simpson, Medill, & McLoughlin, ). Lastly, in line with the EPP hypothesis, we predicted that a freshwater availability effect on male mating inequality would vary among years, as the annual amount of rainfall that recharges the island's water table and influences freshwater availability has been shown to underlie spatially dynamic polygyny thresholds in this system (Manning & McLoughlin, ).…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations